Partnerships for development and the provision of water and sanitation: Conditions and limits - Marianne Beisheim; Hannah Janetschek; Johanna Sarre (Stiftung Wissenschaft und Politik (SWP), 2011)
During World Water Week in August 2011 - entitled »Water in an Urbanizing World« - UN agencies, experts, and donors will once more be promoting transnational public-private partnerships as a promising and innovative instrument for the effective provision of water and sanitation. In reality, however, many of them turn out to have deficiencies; some are even outright failures. There are specific conditions for success, and there are limits to these partnerships when used in difficult settings or for complex tasks. If the UN wants its partnerships to effectively contribute toward the realization of the Millennium Development Goals or other international goals, it needs to monitor and assess them in a more systematic manner. The Rio+20 United Nations Conference on Sustainable Development in 2012 is a chance to initiate the necessary reforms
Keywords: 320